THE DIFFERENCE OF ARCH PROFILES BETWEEN SCHOOLCHILDREN WITH AND WITHOUT FREE MEAL PROGRAM - Maria Laurentia Sanjaya; Jennifer Widjaja; Nurfitri Amaliah (Dentino: Jurnal Kedokteran Gigi, 2026)
Introduction: The development of the dental arch in childhood is influenced by nutritional status, masticatory habits, and orofacial functional stimulation. Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) is a school-based nutritional intervention that may positively affect jaw growth by providing nutrient-rich foods with appropriate textures. This study aimed to compare maxillary and mandibular arch dimensions between children participating in the MBG program and those not enrolled in the program. Methods: A cross-sectional study was conducted among children aged 10–12 years who met the inclusion criteria from two elementary public schools. Intercanine width, intermolar width, arch length, and arch depth were measured on dental cast models. Data were statistically analyzed to assess differences between the MBG and non-MBG groups. Mann-Whitney test was used for non-normally distributed data, while T-test was used for normally distributed data. Results: Several dental arch parameters, including maxillary intercanine width, maxillary arch length, mandibular intermolar width, and mandibular arch length, were significantly greater in the MBG group compared to the non-MBG group (p < 0.05). Conclusion: Participation in the MBG program appears to support transverse and sagittal dental arch development, potentially through enhanced masticatory function and improved daily nutritional intake. These findings highlight the clinical relevance of school-based nutritional interventions as a promotive strategy for children’s oral health and early malocclusion prevention. Keywords: Free nutritious meal program, Jaw development, Malocclusion